An empirical analysis of government debt in selected Western Europe countries: does productivity matter? - Chu, Wen Ni; Chua, Sin Keat; Chuah, Xung Wei; Lee, Qian Qi; Soo, Zhi Cheng (2019)
This research attempts to examine the relationship between macroeconomic factors like GDP growth, tax revenue and productivity as well as political factors like corruption on the government debt. This is a secondary-based research whereby all the data was collected from 2001-2016 from World Bank Database and OECD Database. The sample countries comprise of selected 16 West Europe countries. Due to the fact that this is a panel data, therefore this research is employing FEM model to examine the relationship. The empirical result showed that GDP growth rate and corruption has negative expected sign to the government debt whereas productivity has a positive impact on the government debt. In the process of further testing the interaction term of productivity on other variables, the result showed that productivity & GDP growth as well as productivity & corruption both has a positive relationship to the government debt. The tax revenue is neither significant in basic model nor model with interaction term. Hence, it is insignificant. Although this research has some limitations, yet the study still is a good reference for parties like government and researchers on the relationship of those variables on the government debt.